Layanan Konseling Individu Dengan Teknik Self Management Untuk Meningkatkan Kontrol Diri (Studi Kasus Pada Klien â€œAâ€ Di Yayasan Mitra Mulia Banyuasin) - Yayan Erpansyah; Suryati; Zhila Jannati (CV. ITTC INDONESIA, 2023)
Individual counseling is a counseling service provided by a counselor to a client with individual meetings, meaning that the meeting is carried out face to face by two people called the counselor and the client, to help the client solve their problems and aims to enable the client to actualize himself and the client in the future. can solve the problems that exist in him. In conducting individual counseling, researchers use self-management techniques, which is a process where clients direct changes in their own behavior, using one strategy or a combination of strategies. So, in the counseling process, even though the counselor encourages and trains this procedure, it is the counselor who has full control. The use of self-management techniques can help counselors to easily research clients and also the shortcomings of this technique. In this research, researchers used a qualitative approach with a case study research method. A qualitative approach is a way to explore and understand social problems being faced by individuals or groups of people. The process is more important than the results, analysis in qualitative research tends to be carried out inductively and meaning is essential. Based on the research results, the self-control that client